Extraordinary Pricing of Orphan Drugs: Is it a Socially Responsible Strategy for the U.S. Pharmaceutical Industry? - Hemphill, Thomas A. (Journal of business ethics, 2010)
The PRIME Institute of the College of Pharmacy, University of Minnesota, recently released preliminary research findings indicating a trend of extraordinary pharmaceutical industry pricing of drug products in the United States (U.S.). According to researchers at the PRIME Institute, such extraordinary price increases are defined as any price increase that is equal to, or greater than, 100% at a single point in time. In some instances, PRIME Institute researchers found that drugs exhibiting extraordinary price increases are categorized as “orphan drugs” (or blood-related biologic treatments) and often life-saving or life-sustaining for treating the cause or symptoms of diseases affecting fewer than 200,000 people in the U.S., or where there is prevalence of less than 5 per 10,000 people afflicted with a disease or symptoms in the community. Because of extraordinary price increases for orphan drugs – some exceeding 1000% at a single point in time – this article addresses two interrelated questions: Are extraordinary orphan drug price increases socially responsible behavior? If so, are the pharmaceutical industry's policies providing orphan drug access to American consumers in dire need of available life-sustaining and life-enhancing pharmaceuticals considered “socially responsible” behavior? The author concludes, after an interdisciplinary analysis of the legal, economic, sociopolitical, and ethical dimensions of orphan drug pricing, that they are not socially responsible – unless justified by cost and availability of health care marketplace/patient options. Furthermore, the author recommends a socially responsible industry strategic approach to insure that patients ultimately receive – regardless of cost – timely access to life-saving and life-sustaining orphan drugs.